Effect of 𝘽𝙚𝙖𝙪𝙫𝙚𝙧𝙞𝙖 𝙗𝙖𝙨𝙨𝙞𝙖𝙣𝙖 and 𝘽𝙖𝙘𝙞𝙡𝙡𝙪𝙨 𝙩𝙝𝙪𝙧𝙞𝙣𝙜𝙞𝙚𝙣𝙨𝙞𝙨 on Hemocytes of Mealworm Beetle Larvae (𝙏𝙚𝙣𝙚𝙗𝙧𝙞𝙤 𝙢𝙤𝙡𝙞𝙩𝙤𝙧 L.) - Suwannakhon, Narutchala; Sintusopha, Tidarat; Pawasena, Nilawan; Tatan, Nujira; Tungjitwitayakul , Jatuporn (Burapha Science Journal, 2024)
Background and Objectives : Biopesticides have been used to control and eliminate pests widely. However, the information on how insect’s hemocytes respond to biopesticides is still limited. The aim of this study was to examine the effect of Beauveria bassiana and Bacillus thuringiensis on insect’s hemocytes using the mealworm beetle (Tenebrio molitor L.) larva as an animal model. Methodology : The total hemocyte count (THC) and differential hemocyte count (DHC) were examined after T. molitor larvae were treated with biopesticides at concentrations of 0.0025, 0.00625 and 0.0125 g/ml for 24, 48, 72, 96, 120, 144 and 168 hours. Main Results : Results showed that THC was decreased significantly in the larvae treated with B. bassiana and B. thuringiensis at 24 hours and remained low thereafter. Moreover, the changes in THC were examined in larvae treated with 0.0125 g/ml of biopesticides for 2, 6, 10, 24, 48 and 72 hours. The THC in larvae treated with B. bassiana started to decrease at 6 h, while the decrease in TCH was recorded at 2 h after the larvae were treated with B. thuringiensis. The DHC in larvae treated with B. bassiana and B. thuringiensis were found in 4 types. Prohemocytes was the dominant hemocytes found in the control larvae, but number of prohemocytes decreased significantly when the larvae were treated with B. bassiana and B. thuringiensis at every concentration for 24 hours. Plasmatocytes increased in all examined concentrations and all periods of treatment. Granulocytes responded differently to B. bassiana and B. thuringiensis. The number of granulocytes increased when the larvae were treated with B. thuringiensis at 48 and 72 hours, while the decrease of granulocytes was recorded with highest concentration at 120-168 hours after B. bassiana treatment. In contrast, the number of oenocytes was not changed after biopesticide treatment. Conclusions : The results indicated the treatment of biopesticides affected the THC and DHC in the T. molitor larvae. This finding provides basic information on how biopesticides affected the immune system in insects.